REPRESENTATION OF THE MEN STEREOTYPES IN THE STRUCTURE AND SEMANTICS OF POLISH PHRASEOLOGISMS - Bieliajeva, І. G.; Dembitskii, D. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article characterizes major features of the men stereotypes in the structure and semantics of polish phraseologisms.